ORGANIZATION OF PRIMARY SEED-GROWING OF SOYBEAN - O. V. Ermolina; O. V. Korotkova; A. A. Lysenko (Зерновое хозяйство России, 2018)
The article reveals basic problems of soybean seed-growing, considers the problems of maintaining of cultivars purity and shows distinctive features of the cultivars. It also sets out indicators of soybean quality and gives their values according to GOST.  Because seed quality and genetic homogeneity of a cultivar depend upon both time of reproduction and compliance of cultivation technology, the article reveals technological methods of soybean cultivation, i.e. a place in crop rotation, peculiarities of general and seedbed preparation, a choice of methods and terms of sowing, seeding rates, measures of care for crops and defense from pests and diseases, peculiarities of harvesting and post-harvesting processing and seed storage. The recommendations about optimal soil temperature, seeding rates have been given for the cultivars of different groups of ripeness depending on width of row spacing and depth of seeding.  The article deals with the problems of soybean care and the most widespread herbicides for weed control, terms and doses of application. The most harmful pests, permitted substances and doses of application for their control have been listed in the work. We also recommended methods of adjusting soybean harvesters and equipment which can be used for drying and cleaning of seeds. The technology of seed storage is considered in the paper as well. A set of measures to receive soybean seeds with high seeding properties has been recommended.We suppose its fulfillment can increase quality of primary seed-growing, providing all farms of Rostov region with highly reproductive soybean seeds.